The principal RTAs comprising ACP States - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Organization of Eastern Caribbean States (OECS): Antigua and Barbuda, Dominica, Grenada, Montserrat, St. Kitts and Nevis, St. Lucia and St. Vincent and the GrenadinesCaribbean Community (CARICOM): Antigua and Barbuda, the Bahamas, Barbados, Belize,...